2011
DOI: 10.1038/gene.2010.68
|View full text |Cite
|
Sign up to set email alerts
|

The human G1m1 allotype associates with CD4+ T-cell responsiveness to a highly conserved IgG1 constant region peptide and confers an asparaginyl endopeptidase cleavage site

Abstract: The human G1m1 allotype comprises two amino acids, D12 and L14, in the CH3 domain of IGHG1. Although the G1m1 allotype is prevalent in human populations, ∼40% of Caucasiods are homozygous for the nG1m1 allotype corresponding to E12 and M14. Peptides derived from the G1m1 region were tested for their ability to induce CD4+ T-cell proliferative responses in vitro. A peptide immediately downstream from the G1m1 sequence was recognized by CD4+ T cells in a large percentage of donors (peptide CH315−29). CD4+ T-cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 46 publications
0
14
1
Order By: Relevance
“…58 Interestingly, one study reported increased in vitro CD4 T cell responsiveness to peptides derived from G1m1 antibodies in donors homozygous for the non-G1m1 allele versus those homozygous for the G1m1 allele. 61 However, a cohort study comprising 250 adalimumabtreated RA patients examined the formation of anti-adalimumab antibodies and determined their binding to the G1m17,1 allotype, and anti-allotype antibodies were detected in none of the patients. 62 Another cohort study examined anti-allotype antibody formation in 118 Crohn's disease patients treated with infliximab.…”
Section: Anti-allotype Antibodiesmentioning
confidence: 99%
“…58 Interestingly, one study reported increased in vitro CD4 T cell responsiveness to peptides derived from G1m1 antibodies in donors homozygous for the non-G1m1 allele versus those homozygous for the G1m1 allele. 61 However, a cohort study comprising 250 adalimumabtreated RA patients examined the formation of anti-adalimumab antibodies and determined their binding to the G1m17,1 allotype, and anti-allotype antibodies were detected in none of the patients. 62 Another cohort study examined anti-allotype antibody formation in 118 Crohn's disease patients treated with infliximab.…”
Section: Anti-allotype Antibodiesmentioning
confidence: 99%
“…In effect, our results are concordant with the initial hypothesis involving induction of immune responses against the incompatible allotype of INX. These immune responses could include anti-allotype antibodies [ 16 , 17 , 19 ] or a T cell response independent of anti-allotype antibodies [ 18 ]. The anti-allotype antibodies would target the INX molecule leading to its accelerated clearance.…”
Section: Discussionmentioning
confidence: 99%
“…Our approach, at the DNA level instead of the anti-allotype antibodies, has avoided these technical difficulties, has permitted us to use patients lacking sera at the relevant point in the treatment course, and allows for other forms of involvement of the allotypes beyond the induction of antibodies. One of these alternative mechanisms is a different type of immune response against the G1m1 allotype that involves CD4 T cell activation and production of cytokines [ 18 ]. The T cell antigen does not include the allotype but a nearby peptide that becomes accessible to antigen processing and presentation because the G1m1 allotype introduces an asparaginyl endopeptidase cleavage site [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations